Investigation of prosocial and antisocial behaviors of young athletes in terms of moral decision making attitudes - S. Alemdag (H.S. Skovoroda Kharkov National Pedagogical University, 2019)
Purpose: The aim of this study is to investigate the prosocial and antisocial behaviors of young athletes in terms of their moral decision making attitudes. Material: The study group consists of male athletes, aged among 13-17, who are licensed in the infrastructure of amateur and professional sports clubs in Trabzon/Turkey. "Attitudes to Moral Decision-making in Youth Sports Questionnaire (AMDYSQ)" and "Prosocial and Antisocial Behavior in Sports Scale (PABSS)" was used as a data collection tool. Descriptive statistics, MANOVA, and correlation were used to analyze the data. Results: As a result of the study, while the athletes' prosocial and antisocial behaviors do not show a significant difference according to the sporting year variable, the moral decision-making attitudes of the athletes show a significant difference according to the sporting year variable. In addition, as a result of the correlation analysis, it was observed that there were low and medium positive and negative relations between the sub-factors of the prosocial and antisocial behavior and the moral decision-making attitudes of young athletes.Conclusions: The present study indicated that good moral attitudes positively contributed to prosocial and antisocial behaviors during the competition.